Transcriptomics of the Anthopleura Sea Anemone Reveals Unique Adaptive Strategies to Shallow‐Water Hydrothermal Vent - Mei‐Fang Lin; Li‐Lian Liu; Chen‐Tung Arthur Chen (Ecology and Evolution)
ABSTRACT The nonsymbiotic sea anemone Anthopleura nigrescens dominates the shallow‐water hydrothermal vents off the coast of Kueishan Island, Taiwan. These vents represent some of the world's most extreme environments, with recorded pH values as low as 1.52 and temperatures reaching 121°C. To investigate the adaptations of A. nigrescens to these extreme conditions, transcriptomic analyses were conducted to compare populations inhabiting vent and non‐vent areas. To identify shared genetic mechanisms in vent‐dwelling anemones, specific orthologs conserved in vent sea anemones were identified by comparing the genomic data of Anthopleura species and other sea anemones. Tank experiments with elevated temperatures were also performed to evaluate the expression profiles of genes associated with heat resistance. The transcriptomic analysis revealed that enriched genes in vent populations are involved in H2S homeostasis and stress resistance, suggesting that detoxification and thermal stress resistance are critical adaptive strategies. Two significantly upregulated genes encoding hydroxyacylglutathione hydrolase and thiosulfate sulfurtransferase may play a role in managing sulfur toxicity and maintaining redox balance. The enriched genes and vent‐specific gene expression patterns also suggest that efficient DNA repair mechanisms play a crucial role in the thermal stress resistance of vent populations. Interestingly, some genes associated with circadian rhythms were upregulated in vent populations, suggesting these genes may help vent anemones adapt to the highly dynamic conditions of hydrothermal vents. Furthermore, the expression profiles of stress‐resistance‐related genes reveal that vent anemones have developed unique molecular regulatory mechanisms to cope with elevated temperatures, as observed in the tank experiment. These transcriptomic findings advance our understanding of the life adaptations in shallow‐water hydrothermal vent environments.